2010
DOI: 10.1136/bmj.c2161
|View full text |Cite
|
Sign up to set email alerts
|

Short term impact of smoke-free legislation in England: retrospective analysis of hospital admissions for myocardial infarction

Abstract: Objective: To measure the short term impact on hospital admissions for myocardial infarction of the introduction of smoke-free legislation in England on 1 July 2007. Design: An interrupted time series design with routinely collected hospital episode statistics data. Analysis of admissions from July 2002 to September 2008 (providing five years' data from before the legislation and 15 months' data from after) using segmented Poisson regression. Setting: England. Population: All patients aged 18 or older living i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
113
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(129 citation statements)
references
References 52 publications
12
113
1
1
Order By: Relevance
“…This legislation has resulted in substantial population health gain, including reductions in workplace exposure to secondhand smoke (SHS), 1 increased smoking quit rates, 2 and decreased hospital admissions for acute myocardial infarction. 3,4 A small number of studies conducted in North America have found that making public places and workplaces smokefree reduces hospital admissions and emergency department visits for asthma. [5][6][7] A Scottish study also found that the introduction of comprehensive smoke-free legislation in March 2006 was associated with a reduction in hospital admissions for childhood asthma.…”
Section: Resultsmentioning
confidence: 99%
“…This legislation has resulted in substantial population health gain, including reductions in workplace exposure to secondhand smoke (SHS), 1 increased smoking quit rates, 2 and decreased hospital admissions for acute myocardial infarction. 3,4 A small number of studies conducted in North America have found that making public places and workplaces smokefree reduces hospital admissions and emergency department visits for asthma. [5][6][7] A Scottish study also found that the introduction of comprehensive smoke-free legislation in March 2006 was associated with a reduction in hospital admissions for childhood asthma.…”
Section: Resultsmentioning
confidence: 99%
“…In this instance, smoking's reproduction was dependent on the various practices that make up the life of a Samurai, including craftsmanship, combat training and ceremony. More recently, practices of smoking and drinking in pubs and clubs or smoking and going out for a meal in a restaurant were strongly interconnected in the UK, until the ban on smoking in public places (Bauld, 2011;Sims, Maxwell, Bauld, & Gilmore, 2010). In various other parts of the world, these close connections persist; but in the UK at least, eating at a restaurant and smoking, and drinking in a bar and smoking, are currently incompatible.…”
Section: Theories Of Practicementioning
confidence: 99%
“…by making it more difficult to find a place to smoke), affect competences (knowing where and when not to smoke) and even meanings (by reducing the sociability of smoking for example). Banning smoking in public places has consequently made a real difference (Bauld, 2011;Sims et al, 2010) not only to levels of smoking, but also to understandings of where smoking might go on.…”
Section: Implications For Public Health Policymentioning
confidence: 99%
“…This powerful quasiexperimental design is able to estimate intervention effects while taking into account underlying trends, thus ensuring that post-intervention changes are not merely continuations of longer-term trends. This method has been employed recently in the evaluation of a range of tobacco control policies [18][19][20][21][22]. While an interrupted time-series analysis cannot disentangle the effects of multiple interventions that are introduced at the same time, we are unaware of any interventions being implemented around the time of the freeze that are likely to have substantially influenced our outcomes.…”
Section: -Week Quittersmentioning
confidence: 99%